Engineered tissue inhibitor of metalloproteinases-3 variants resistant to endocytosis have prolonged chondroprotective activity - Doherty, C; Visse, R; Dinakarpandian, D; Strickland, D; Nagase, H; Troeberg, L (American Society for Biochemistry and Molecular Biology, 2016)
Tissue inhibitor of metalloproteinases-3 (TIMP-3) is a central inhibitor of matrix-degrading and sheddase families of metalloproteinases. Extracellular levels of the inhibitor are regulated by the balance between its retention on the extracellular matrix and its endocytic clearance by the scavenger receptor low density lipoprotein receptor-related protein 1 (LRP1). Here, we used molecular modeling to predict TIMP-3 residues potentially involved in binding to LRP1 based on the proposed LRP1 binding motif of 2 lysine residues separated by about 21 Å and mutated the candidate lysine residues to alanine individually and in pairs. Of the 22 mutants generated, 13 displayed a reduced rate of uptake by HTB94 chondrosarcoma cells. The two mutants (TIMP-3 K26A/K45A and K42A/K110A) with lowest rates of uptake were further evaluated and found to display reduced binding to LRP1 and unaltered inhibitory activity against prototypic metalloproteinases. TIMP-3 K26A/K45A retained higher affinity for sulfated glycosaminoglycans than K42A/K110A and exhibited increased affinity for ADAMTS-5 in the presence of heparin. Both mutants inhibited metalloproteinase-mediated degradation of cartilage at lower concentrations and for longer than wild-type TIMP-3, indicating that their increased half-lives improved their ability to protect cartilage. These mutants may be useful in treating connective tissue diseases associated with increased metalloproteinase activity.